Microvascular Response in Patients with Complex Regional Pain Syndrome as Measured by Laser Doppler Imaging. (July 2016) - Gorodkin, Rachel; Herrick, Ariane L.; Murray, Andrea K.
Abstract: Objectives: Our aim was to investigate the hypothesis that microvascular dysfunction occurs in patients with CRPS. Specifically, whether there were functional differences in either deeper cutaneous blood vessels or more superficial nutritive vessels between the affected and unaffected limb in patients with CRPS, and between CRPS patients and healthy control subjects. Methods: Twenty‐two patients with CRPS (five male; mean age 45 years; eight upper limb involvement, 14 lower limb) and 23 healthy control subjects (one male; 43 years) were recruited. Microvascular flow at affected and unaffected contralateral sites was measured, following local heating, using laser Doppler imaging (red/green wavelengths). Corresponding sites were imaged in healthy controls. Maximum flux level and area under the curve (first 20 scans, AUC20) were measured. Results: Vasodilator responses to heat were similar in affected and unaffected limbs, and in healthy controls. For example, median (IQR) "red" AUC20 in CRPS was 138.6 (120.0–152.9)% change from baseline in affected limb and 135.0 (120.7–166.8)% in unaffected limb, and (in healthy controls) 133.1 (117.2–145.9)% and 139.1% (126.0–162.1) in limb 1 and 2. Conclusions: We found no impairment of vasodilation in cutaneous microvessels in CRPS. The vasomotor changes in CRPS may relate to larger vessel dysfunction.